Implementation of School-Based Management: The Role of School Committees in the Preparation of Revenue and Cost Budget Plans - Dwiyama, Fajri; Nurlaelah, Nurlaelah; Hakim, Ahmad; Setiawati, Nur; Arimah, Haerunnisa Nur (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This study examines the implementation of school-based management, especially the role of school committees in the preparation of budgets and revenue plans at SMKN 1 Bone. This research aims to identify and document the key roles of the School Committee, analyze the process of preparing budgets and revenue plans, and highlight the committee's contribution to this process. Qualitative research methods were used, utilizing social and management approaches to understand the role of committees in preparing the School Budget and Revenue Plan (RAPBS). Data was collected through observation, interviews, and documentation, involving primary sources such as committee chairs, secretaries, principals, and educational staff, along with secondary data from related literature. The findings reveal that the committee acts as an advisor, supporter, supervisor, and liaison between the school and parents. They play an active role in meetings with schools, offering input and approving the RAPBS. The committee also handles parents' concerns, evaluates school needs, and provides financial support. In addition, they oversee the school's financial management, organize community support, and identify critical resources for the preparation of the RAPBS.